Digital platform ecosystems in flux: From proprietary digital platforms to wide-spanning ecosystems - Jan Frederic Nerbel; Markus Kreutzer (Electronic Markets, 2023)
Digital Platform Ecosystems (DPEs) represent a distinct form of interorganizational relationship cultivated on digital infrastructures. Although DPEs are researched extensively among management scholars, shortcomings in formalizing their emergence remain. Particularly re-occurring patterns and temporal dimensions of emergence continue to be relatively unexplored. We review existing literature in an integrative manner and shed light on DPE emergence by deriving a framework comprising four distinct stages. We thereby sharpen the understanding of DPEs and bring convergence to an increasingly fragmented field of research by accounting for industrial innovation management, organizational, market-based, and ecosystem-based views. As a result, we present a classification of DPE emergence stages and related key activities contributing to the progression from a nascent digital platform into a wide-spanning DPE. Finally, we propose multiple avenues for future research.
Keywords: M1; 620; Ecosystem; Platform; Emergence; Complementarity